A systematic review of the prevalence of selected sexually transmitted infections in young people in Latin America - María Teresa Vallejo-Ortega; Hernando Gaitán Duarte; Maeve B. Mello; Sonja Caffe; Freddy Perez (Pan American Health Organization, 2022)
Objective. To estimate the burden of Chlamydia trachomatis (CT), Neisseria gonorrhoeae (NG), Treponema pallidum (TP), and human papillomavirus (HPV) infections among people aged 10 to 25 in Latin America and the Caribbean. Methods. The MEDLINE, EMBASE, and LILACS databases were searched, as well as documents from regional organizations or national health Institutions. Population-based studies that reported prevalence or incidenceof CT, NG, TP, and HPV detected through confirmatory tests in adolescents and young people were included. Two reviewers independently selected studies and extracted data. The quality of studies was assessed using the Newcastle-Ottawa Scale. Pooled estimators were calculated in cases where heterogeneity was <70%; when not feasible, prevalence ranges were reported. Results. Out of a total of 3 583 references, 15 prevalence studies complied with the inclusion criteria. Due to substantial heterogeneity (>70%), it was not possible to pool frequency estimators. Among the general population, the prevalence of CT infection ranged between 2.1% and 30.1% (9 studies, 5 670 participants); for NG, prevalence ranged between 0% and 2.9% (8 studies, 5 855 participants); for TP, prevalence varied between 0% and 0.7% (3 studies, 11 208 participants), and for HPV infection, prevalence ranged between 25.1% and 55.6% (8 studies, 3 831 participants). Conclusions. Reliable, population-based data on sexually transmitted infections (STIs) in adolescents and youth in Latin America and the Caribbean are limited. Additional studies are needed to better understand the burden of STIs in this population. However, given the substantial prevalence of STIs detected, countries need public health policies for prevention, early diagnosis, and treatment of STIs in young people.